Nuclear Decommisioning in the EU: Financing Issues - A. V. Zimakov (Контуры глобальных трансформаций: политика, экономика, право, 2022)
Decommissioning of nuclear power plants is increasingly becoming one of heavily discussed issues in the controversy over admissibility of nuclear power as a low-carbon technology in the climate-neutral Europe by 2050 in the face of rising shut-down reactors numbers. The rise of the due to be dismantled reactors figures is to be explained by ageing reactorfleet, nuclear phase-out decisions in several EU countries and by the change from deferred to immediate dismantling strategy. Being a quite costly undertaking, immediate dismantling of a nuclear facility requires financial resources that should be sufficient and available by the beginning of dismantling activities. Despite the commonly accepted “polluter pays” principle that means that the nuclear facility owner should provide necessary financing for decommissioning, there are several cases in Europe when the costs of dismantling activities are borne by the state or even by the budget of the European Union. The general reason for that is the lack of financial resources accumulated by the nuclear facility owner. The European Union has timely recognized the potential risk of lacking decommissioning financing and has stepped up certain pro-active measures in a form of non-binding recommendations on the management of decommissioning funds and binding Euratom directive setting ultimate responsibility of the state for nuclear waste utilization. The Euratom directive that is to be transposed into national legislation requires a creation of a legal framework ensuring safe accumulation of sufficient financial resources for decommissioning of nuclear facilities and further waste utilization. By these actions, the European Commission prompts the member states to get more involved into regulation of nuclear decommissioning financing thus preventing shortages requiring the state or even the EU to step in. Being far from a closed issue, the situation in decommissioning financing in the EU is gradually improving. Ultimately, the extensive decommissioning volumes coupled with available financing is making Europe a very attractive decommissioning market with a potential to overtake the global leadership in nuclear decommissioning.